Author Correction: Potential health and economic impacts of dexamethasone treatment for patients with COVID-19 - Águas, Ricardo; Mahdi, Adam; Shretta, Rima; Horby, Peter; Landray, Martin; White, Lisa; Arifi, Fatima; Zhumalieva, Chynar; Lubis, Inke N. D.; Monteiro, Antoninho Benjamin; Moldokmatova, Ainura; Chen, Siyu; et al. (Springer Nature, 2021)
The original version of this Article contained an error in the author affiliations. The affiliation of Amirah Azzeri with Department of Primary Care, Faculty of Medicine and Health Sciences, Universiti Sains Islam Malaysia (USIM) was inadvertently omitted. This has now been corrected in both the PDF and HTML versions of the Article.
Author Correction: Potential health and economic impacts of dexamethasone treatment for patients with COVID-19 (Nature Communications, (2021), 12, 1, (915), 10.1038/s41467-021-21134-2)